The Optimum Protein Content in High-Energy Starter Diet for Chukar Partridge (Alectoris chukar chukar) - Ozek, Kasim (International Journal of Poultry Science, 2006)
The optimum protein content in high-energy starter diet was investigated in the experiment. The birds were fed one of the 6 isocaloric (3200 kcal/kg Metabolizable energy) diets containing 18, 20, 22, 24, 26, and 28 % protein from hatch to 8 weeks of age. Body weight, feed consumption and feed conversion ratio of partridges were examined in the experiment. There were no significant effects of the protein content in high-energy starter diet on the body weight at any age. According to the result of the present experiment chukar chicks does not need high protein in high-energy starter diet when with supplemented methionine and lysine. The best results of feed conversion and feed consumption were observed in partridges fed 24 % protein.